Censorship and deaf ears faced with the literature on the death camps in post-war Europe: Joaquim Amat-Piniella and Primo Levi - Pérez Vidal, Alejandro (Hispania Nova, 2019)
The present study considers some aspects of the remembrance of concentration camp experiences in the years immediately following World War II. The first part focuses on the publishing history of K.L. Reich, by Joaquim Amat-Piniella, pointing out specially its partial publication in France in 1945 and a project to publish the whole novel in Barcelona in 1948. The second part seeks to explain the limited success of K.L. Reich when it was first published, by considering what happened to similar works in other European countries and, in particular, Primo Levi’s Se questo è un uomo. It argues that the anti-communism of the Cold War left little room for the public remembrance of the concentration camps and that it was the anti-fascist leftists who were most inclined to keep this memory alive.